Strengthening the correctional system through electronic supervision of prisoners: A comparative legal study for reforming Indonesia's penitentiary law - Widyawati, Anis; Purnomo, Didik; Setyanto, Heru; Suryani, Leony Sondang; Fitha Ayun Lutvia Nitha (Jurnal Hukum Novelty, 2025)
Introduction to the Problem: The practice of criminal law in a country should evolve technologically, as in Indonesia, where electronic surveillance of prisoners has been adopted. Indonesia has correctional facilities that are experiencing tremendous overcrowding, and this trend not only hinders the effective rehabilitation of inmates but also burdens the state coffers. Countries with well-organised biobanks have used this surveillance technology to prevent this malfunction. Purpose/Study Objectives: This research aims to analyze whether there is a possibility of introducing electronic monitoring of prisoners in Indonesia as a possible amendment to the Criminal Sanctions Implementation Act by conducting an international review of the experience of similar practices in several countries with civil law (Latvia, Iceland, France, Norway, Croatia, Kosovo), common law (England and Wales), and mixed law (Thailand) systems. Design/Methodology/Approach: This research utilises qualitative approaches, especially normative legal analysis and comparison. The data was collected by way of thorough analysis of legal documents from different jurisdictions that have varying legal traditions, such as civil law countries like Latvia, Iceland, France, Norway, Croatia, and Kosovo, common law countries of England and Wales, and Thailand, which has a mixed legal system. The comparison of these legal systems assists in constructing possible integration of electronic surveillance systems in the criminal law system in Indonesia. Findings: Research shows that electronic monitoring of prisoners in Indonesia has potential despite the lack of legislation for such tracking due to the relevance of implementation, especially for low-risk prisoners and first-time offenders. Concerns are identified, such as inadequate infrastructure, lack of comprehensive legislation and resistance from various groups. However, the promising benefits outweigh those concerns, as well as features such as a 40% reduction in prison overcrowding and improvements in recidivism rates of inmate rehabilitation. Paper Type: Research Article